Therapeutic response analysis in dogs with naturally occurring osteoarthritis. (November 2017) - Gagnon, Alexandre; Brown, Dominique; Moreau, Maxim; Lussier, Bertrand; Otis, Colombe; Troncy, Eric
Abstract: Objective: Reporting the rate of positive (+) and negative (–) responders based on an objective outcome measure of pain-related functional disability/lameness in dogs with naturally occurring osteoarthritis (OA), and the relationship between initial lameness severity and the odds of being a (+) responder. Study design: Retrospective analysis of published peer-reviewed clinical trials in dogs with naturally occurring OA. Animals: Dogs ( n  = 213) with hip and/or stifle afflicted-joints. Methods: A responder analysis was undertaken using a previously determined cut-off value of ±2.0% of body weight using the peak of vertical force (PVF). Among the selected trials, PVF was acquired under similar conditions. Therapeutic approaches were therapeutic diets, natural health products and nonsteroidal anti-inflammatory drugs. Results: Among dogs receiving a therapeutic approach as described above ( n = 121), 62.8% [95% confidence interval, 53.9–70.9] were defined as (+) responders, whereas 11.6% [7.0–18.5] were (–) responders, accounting for a net (+) response rate by 51.2% [42.0–60.4]. In dogs receiving a negative control ( n = 92), the net (+) response rate was 1.1% [0.0–5.9]. The number needed to treat was 4, and the effect size 0.7 [0.4–1.0]. The odds ratio of being a (+) responder under the therapeutic approaches was 2.85 [1.57–5.17] ( p < 0.001). For every less severe lameness manifested with an increment in PVF by 1% body weight, the chance of being a (+) responder following treatment decreased by 9% (odds ratio 0.91 [0.86–0.97], p = 0.006). Conclusion and clinical relevance: The rate of (+) responder optimizes decision making for the management of pain-related clinical signs of OA. Evidence-based medicine was further supported by clinical metrics based on an objective outcome measure of pain-related functional disability/lameness. This study also revealed that dogs with a mild lameness are less prone to be improved, emphasizing the need to carefully manage OA dogs in spite of a more subtle affliction.